Aspirin for Prevention of Preeclampsia in Lupus Pregnancy. (20th March 2014) - Schramm, Amelie M.; Clowse, Megan E. B.
Abstract : Preeclampsia, the onset of hypertension and proteinuria during pregnancy, is a common medical disorder with high maternal and fetal mortality and morbidity. The underlying pathology remains poorly understood and includes inflammation, endothelial dysfunction, and an unbalanced thromboxane A2 /prostacyclin ratio. For women with systemic lupus erythematosus (SLE), particularly those with preexisting renal disease or with active lupus, the risk of developing preeclampsia is up to 14% higher than it is among healthy individuals. The mechanism is still unknown and the data for preventing preeclampsia in lupus pregnancies are rare. Modulating the impaired thromboxane A2 /prostacyclin ratio by administration of low-dose aspirin appears to be the current best option for the prevention of preeclampsia. After providing an overview of the pathogenesis of preeclampsia, preeclampsia in lupus pregnancies, and previous trials for prevention of preeclampsia with aspirin treatment, we recommend low-dose aspirin administration for all lupus patients starting prior to 16 weeks of gestation. Patients with SLE and antiphospholipid syndrome should receive treatment with heparin and low-dose aspirin during pregnancy.